A rare and unique experience of a blunt intrathoracic traumatic injury of the trachea and its management in South Africa: a case report - Rudo Mutsa Vanessa Pswarayi; Anna Katariina Kerola (Journal of Trauma and Injury)
Blunt intrathoracic tracheal injuries are rare, even among blunt chest trauma patients. An early diagnosis based on a high index of suspicion allows for timely surgical management of potentially fatal airway trauma, thereby improving overall outcomes. Diagnosing these injuries can be difficult due to their nonspecific clinical features and the occasional difficulty in radiologic diagnosis. If a patient exhibits respiratory compromise with difficult ventilation and poor lung expansion, despite the insertion and management of an intercostal drain following high-energy blunt trauma, there should be a heightened suspicion of potential airway trauma. The aim of primary repair is to restore airway integrity and to minimize the loss of pulmonary parenchyma function. This case report discusses the rare clinical presentation of a patient with blunt trauma to the intrathoracic airway, the surgical management thereof, and his overall outcome. Although blunt traumatic injuries of the trachea are extremely rare and often fatal, early surgical intervention can potentially reduce the risk of mortality.